Sulphate reducing bacteria (SRB) biofilm development and its role in microbial corrosion of carbon steel - Welikala, Sachie; Al-Saadi, Saad; Gates, Will P.; Panter, Christopher; Singh Raman, R. K. (Frontiers in Materials, 2024)
The development of biofilm by pure SRB culture on carbon steel, and its role on corrosion were investigated using microscopic, spectroscopic, electrochemical and surface characterization techniques. Tubercle biofilm and irregularly shaped pits were observed on steel surfaces in high-nutrients biotic solution. Owing to development of a protective FeS film in 72 h immersion, corrosion resistance improved. In the nutrient-deficient medium, a greater bacterial density attached to the metal surface as the consequence of starved bacteria seeking energy sources from metal. However, electrochemical non-homogeneity developed at the locations of their attachment, that gradually grow over the entire surface.